IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK UNTUK MENANAMKAN NILAIAKIDAH DI MI DARUSSALAM SAMBIROTO BARON NGANJUK TAHUN 2021-2022 - Hidayatul A’yuni (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2024)
Abstract The methods of learning has been applied since the days of Rasul primarilyin memorizing the Koran and what Rasulsays that we know as al-Hadith, whichcertainly containsthe most fundamental thing that is Aqeedah. Aqeedah Islamiyah with six pillars of faith, that are belief in Allah, the angels, the books, the apostles, the end of the day, and Qadha and Qadr both good and bad, has a uniqueness thatis all about the unseen thing (ghaib). People who are actually the most miserableare those who are poor in faith and who have crisis of belief. There is nothing thatcan beatify the soul, clean, pure it, and dispel its anxiety, except the true faith in Allah. From the background of the problem, it is necessary to formulate a problem that will be the focus of research. The researcher formulates the research problem in the form of research questions, namely: How is the teaching pattern of Akidah Akhlak teachers in instilling akidah values ​​in participants at Darussalam Baron Nganjuk, How is the teaching method for Akidah Akhlak teachers in instilling creed values ​​at Darussalam Sambiroto Baron How is the influence of learning the Akidatul Awwam book in instilling the values ​​of faith in students at Darussalam Sambiroto baron, This study focuses on the application of Aqidatul Awam memorization method for strengthening students aqeedah, the method sapplied forestablishing the students faith and making students enjoy learning Aqidatul awwam, and thesuccessof Aqidatul awwam memorization method implemented in Darussalam form sthestrong faith of students. The results of this study can be concluded that there are 3 patterns, namely a one-way pattern, a memorial pattern and an evaluation pattern, while the method used is memorization before entering class, learning akidah material in formal hours, and applying knowledge in student learning activities, while the impact in strengthening akidah students reach eighty-five percent of students' understanding of akidah where in this case Darussalam students already have a good understanding of teaching akidah based on references to the book of Aqidatul Awwam . Keywords: Application Learning, Methods and Implemanting, values students aqeedah